2018
DOI: 10.1177/2333721418804052
|View full text |Cite
|
Sign up to set email alerts
|

Successful Aging in Colombia: The Role of Disease

Abstract: Objective: This study aimed to determine the prevalence of successful aging (SA) and identify its predictive factors in a cohort of older people in the Colombian Andes Mountain. Method: Data were drawn from a prospective longitudinal study of community-dwelling elderly people in Manizales. SA encompassed indicators in four domains: physical, cognitive, emotional, and social functioning. Results: The prevalence of SA was 24.4%. The independent predictors were good and very good self-rated health, middle–high/hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 67 publications
0
19
1
2
Order By: Relevance
“…For instance, while being healthy is important in Western societies, other factors can be important in Eastern societies . In contrast to the results of the present study whose participants were from an Eastern society, a study conducted in Colombia whose participants were from a Western society found that elderly people with chronic diseases had a low perception of successful aging . The difference between the results may have been influenced not only by the cultural characteristics of the societies but also by their perspective on aging.…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, while being healthy is important in Western societies, other factors can be important in Eastern societies . In contrast to the results of the present study whose participants were from an Eastern society, a study conducted in Colombia whose participants were from a Western society found that elderly people with chronic diseases had a low perception of successful aging . The difference between the results may have been influenced not only by the cultural characteristics of the societies but also by their perspective on aging.…”
Section: Discussioncontrasting
confidence: 99%
“…The reduction in the prevalence of robustness among those aged 80 years or older was evidenced in this study. Other studies, despite using different instruments, but similar criteria, also showed that young-old adults are healthier and more robust 2,10,18,20 . However, aging includes multidimensional issues 7,8 with involvement of different predictors, which are influenced in the course of life 1,11,16 .…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, categorization for age groups is different among studies, as well as the methodologies used. Rowe and Kahn's classic proposal 9 , despite the scientific debate about it, continues to significantly influence all discussions on this subject [15][16][17][18][19][20] . Studies on the field are promising, but there is no conceptual consensus or universally standardized instruments for the evaluation 5,15,17,19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations